Productive infection of bovine papillomavirus type 2 in the placenta of pregnant cows affected with urinary bladder tumors. - Sante Roperto (Public Library of Science (PLoS), 2012)
Papillomaviruses (PVs) are believed to be highly epitheliotropic as they usually establish productive infections within stratified epithelia. In vitro, various PVs appear to complete their entire life-cycle in different trophoblastic cell lines. In this study, infection by and protein expression of bovine papillomavirus type 2 (BPV-2) in the uterine and chorionic epithelium of the placenta has been described in four cows suffering from naturally occurring papillomavirus-associated urothelial bladder tumors. E5 oncoprotein was detected both by Western blot analysis and immunohistochemically. It appears to be complexed and perfectly co-localized with the activated platelet-derived growth factor ß receptor (PDGFßR) by laser scanning confocal microscopy. The activated PDGFßR might be involved in organogenesis and neo-angiogenesis rather than in cell transformation during pregnancy. The major capsid protein, L1, believed to be only expressed in productive papillomavirus infection has been detected by Western blot analysis. Immunohistochemical investigations confirmed the presence of L1 protein both in the cytoplasm and nuclei of cells of the uterine and chorionic epithelium. Trophoblastic cells appear to be the major target for L1 protein expression. Finally, the early protein E2, required for viral DNA replication and known to be expressed during a productive infection, has been detected by Western blot and immunohistochemically. Electron microscopic investigations detected viral particles in nuclei of uterine and chorionic epithelium. This study shows that both active and productive infections by BPV-2 in the placenta of pregnant cows can occur in vivo.